Influence of digital competence on teaching readiness through self-efficacy as moderator variable - Rivandi, Rizal; Pahlevi, Triesninda (Indonesian Journal of Educational Development (IJED), 2025)
In the digital era, mastery of technology is a key factor in improving teaching effectiveness. Therefore, pre-service teachers are expected to have good digital competencies to support an interactive and adaptive learning process. This study aimed to analyse the effect of digital competence on teaching readiness of pre-service teachers at the Faculty of Economics and Business (FEB), Universitas Negeri Surabaya (UNESA), with self-efficacy as a moderator variable. This study used a quantitative approach with an explanatory research design, explaining or knowing the relationship between digital competence and self-efficacy in relation to teaching readiness of pre-service teachers at FEB UNESA. This research data analysis technique used Path Analysis. The questionnaire became the main tool for data collection, which was then analysed using path analysis techniques to examine the relationship between digital competence, self-efficacy, and teaching readiness. Recommendations from the results of this study are to improve the teaching readiness of pre-service teachers at FEB UNESA. It is necessary to develop digital competence and self-efficacy through intensive training, integration of technology in the curriculum, lecturer guidance, and teaching practice activities. Collaboration between lecturers, institutions, and students (pre-service) is important to create a supportive learning. Learning programs need to be adaptive to technological developments with the addition of educational technology modules and digital microteaching activities, accompanied by regular evaluations so that development is sustainable.